Reducing Heavy Metal Accumulation in Spring Wheat Grain using Plant Growth Regulators - Merenkov Konstantin; Seregina Inga (BIO Web of Conferences)
In the context of increasing anthropogenic impact on the environment, the problem of crop contamination with heavy metals is becoming increasingly important. Heavy metals such as lead, cadmium, mercury and others can accumulate in soil, water and plants, including grain crops. This can lead to a decrease in the quality of products, which can be potentially hazardous to human health. The studies examined the effect of growth regulators on reducing the level of accumulation of heavy metals in spring wheat grain. Experiments have shown that the use of Biodux and organomineral biopreparation can help reduce the content of heavy metals in wheat grain. The results of the study open up new opportunities for agricultural professionals to enhance product quality using growth regulators. These findings suggest that growth regulators can effectively minimize the risk of heavy metal contamination in crops, making them a valuable tool for spring wheat cultivation. By modifying physiological processes and enhancing plant defense mechanisms, this technology contributes to both improved product quality and environmental protection.